2019
DOI: 10.18488/journal.1005/2019.9.1/1005.1.1.33.46
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vietnam’s Potential Trade: A Case Study of Agricultural Exports to the European Union

Abstract: This study aims at quantifying the determinants of Vietnam’s potential exports to the EU, taking agricultural commodities as a case study. In order to achieve this, we employed a stochastic frontier analysis to estimate Vietnam’s potential agricultural exports, and a system GMM approach to analyze the determinants of the estimated potential agricultural exports of Vietnam. The results showed that Vietnam’s potential agricultural exports to the EU have been high and on an upward trend. In addition, factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…The multiplication variable of Indonesia's real GDP with the real GDP of the importing country (LnRGDPIDN*LnRGDPC) shows a positive sign and is significant up to 1 percent. These results are consistent with other studies such as Linh et al (2019) and Evelyn and Chandran (2019). The variable multiplication of the Indonesian population with the population of the importing country in the previous year (lagLnPOPIDN*LnPOPC) is positive and significant up to 5 percent.…”
Section: Estimation Of Stochastic Frontier Panel Data (Sfpanel) Modelsupporting
confidence: 94%
See 1 more Smart Citation
“…The multiplication variable of Indonesia's real GDP with the real GDP of the importing country (LnRGDPIDN*LnRGDPC) shows a positive sign and is significant up to 1 percent. These results are consistent with other studies such as Linh et al (2019) and Evelyn and Chandran (2019). The variable multiplication of the Indonesian population with the population of the importing country in the previous year (lagLnPOPIDN*LnPOPC) is positive and significant up to 5 percent.…”
Section: Estimation Of Stochastic Frontier Panel Data (Sfpanel) Modelsupporting
confidence: 94%
“…If the value is equal to zero, then the potential export of a product from country i to country j is obtained. Battese & Coelli (1988) and Linh et al (2019) describe the comparison between actual exports and maximum exports when minimum barriers are said to be trade efficiency (exports). Parallel to this concept, the comparison between actual imports and maximum imports in conditions with minimal obstacles is said to be trade efficiency (imports).…”
Section: {( )( }mentioning
confidence: 99%
“…Mỹ & Linh (2017) studied the correlation between Vietnam's agricultural exports and agricultural land area from 1997 to 2014, revealing a negative impact on export turnover. Hoang et al (2019) highlighted positive factors like financial market development, trade freedom, technological readiness, and labor freedom that favorably impact Vietnam's potential agricultural exports to the EU. Nha et al (2020) identified technology, infrastructure, and government policies as significant factors affecting the export of Vietnam's coffee to the EU market.…”
Section: Literature Reviewmentioning
confidence: 99%